2017
DOI: 10.1016/j.stemcr.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Functional Enterospheres Derived In Vitro from Human Pluripotent Stem Cells

Abstract: SummaryIntestinal organoids derived from human pluripotent stem cells (hPSCs) are valuable in vitro research models that enable simplified access to human gastrointestinal tissues. Here, we report the in vitro generation of enterospheres (hEnS) from hPSC-derived gastrointestinal epithelial precursors. hEnS are cystic spheroids with a simple uniform structure composed entirely of intestinal epithelium. hEnS express markers of mature brush border cells and share a transcriptome profile similar to that of more ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…This work provides new insights into intestinal development and maturation during human gestation and should serve as a guide for other researchers studying the intestine, including hPSC-derived tissues, to gauge the relative maturation status of their samples. Our work underscores the difference in the timeline of intestinal development between humans and mice, and reinforces the utility of ex vivo models using human cells and tissues, such as intestinal organoids to further study intestinal development and maturation in humans (Forster et al, 2014;Hill et al, 2017;Nadkarni et al, 2017;Senger et al, 2018;Spence et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This work provides new insights into intestinal development and maturation during human gestation and should serve as a guide for other researchers studying the intestine, including hPSC-derived tissues, to gauge the relative maturation status of their samples. Our work underscores the difference in the timeline of intestinal development between humans and mice, and reinforces the utility of ex vivo models using human cells and tissues, such as intestinal organoids to further study intestinal development and maturation in humans (Forster et al, 2014;Hill et al, 2017;Nadkarni et al, 2017;Senger et al, 2018;Spence et al, 2011).…”
Section: Discussionsupporting
confidence: 64%
“…Our data demonstrates that CHGA is present in the developing epithelium as early as week 13 of gestation, indicating that, similar to mouse, EECs are one of the first differentiated epithelial cell types to emerge in the human intestine Noah et al, 2011). The early emergence of EECs during human intestinal development raises questions as to why EECs are typically absent in intestinal tissues differentiated from hPSCs in vitro (Fordham et al, 2013;Forster et al, 2014;Nadkarni et al, 2017), when other cells types that arise later in development can be found. The lack of EECs could be attributed to deficiencies in exogenous signaling that activate genes responsible for promoting EEC differentiation, such as Neurogenin-3 (Sinagoga et al, 2018;Spence et al, 2011).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Therefore, further maturation of hiPSC-IECs would be required. Procedures that could be useful include heterotopic transplantation into a kidney capsule 24 , transplantation of intestinal grafts prepared by bioengineering technique 26 , co-culture with intestinal neurons 27 and myocytes, suppression of the transcriptional repressor B lymphocyte-induced maturation protein 1 (Blimp1) gene 28,29,30 , and stimulation by diet ingredients.…”
Section: Discussionmentioning
confidence: 99%